Disain Mesin Pengaduk Pakan Puyuh Yang Dilengkapi Dengan Komponen Penyemprot Cairan Fermentasi - Ruzita Sumiati; Fahri Reza; Nandi Pinto; Adriansyah Adriansyah; Yuli Yetri (Department of Mechanical Engineering, Universitas Andalas, 2022)
This study was carried out to deal with reducing feed cost and provide high quality poultry feed for the local breed of quail through the provision of feed mixer machines equipped with fermentation equipment. Mixing feed poultry using machines is much faster, accurate and less energy consuming compered with manual mixing. Poultry feed mixing machine was designed, fabricated and tested. The machine consists of two function as mixing and fermented liquid spray. The design computations to handle a 400 Kg mass of feed and 4 L of fermented liquid. The machine was tested using afeed components divided into 170 kg for Maize bran, 120 kg for bran, 2 kg for mineral, 136 kg for Bone meal , 2 kg for Salt and 4L fermented liquid replicated twice at four mixing durations of 4, 8, 12 and 16 min. The perfect homogenious mixing was got in 16 min